A GENDER PERSPECTIVE IN LANGUAGE USE OF MIDDLE EASTERN FREEDOM ACTIVISTS’ SPEECHES - -, SULISTYANINGTYAS (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: gender perspective, language use, speech, freedom activist, MiddleEast. This research aims to examine the language use of the Middle Eastern freedom activists’ speeches through gender perspective. This research investigates (1) what gender differences in language use showed by male and female Middle Eastern freedom activists’ speeches, and (2) how the language for speech used by male and female speakers influences the audience of the Middle Eastern freedom activists’ speeches.Qualitative approach is used in this research. The data source are from male and female Middle Eastern freedom activists’ speech videos. Then, the data are the speeches of freedom activist which are transcribed into written texts as the primarydata and respondents’ opinion as the secondary data. Three transcriptions from eachgender are considered proper to answer the problems in this research. In analysingthe data, the theories employed are about male and female spoken language differences by Haas (1979) and the language for speech by Jones and Peccei (2004).In answering the second problem of the research, it is also required 10 respondentswith certain criteria.The result reveals that there are sets of spoken language differences between male and female speakers. Male speakers’ language can be characterised as: 1) Form: coarse, direct, using pun, using pronominal apposition, 2) Topic: politics, human relation, 3) Content: using male adjectives, 4) Use: lecture, assert, command. In spite of that, female speakers’ language can be characterised as: 1) Form: polite, 2) Topic: social problem, 3) Content: using hyperbole, using adverb of intensity, 4) Use: non-assertive, tentative. In using the language for speech, both male and female speakers produce metaphor, euphemism, the ‘rule of three’, parallelism, and pronouns in random frequency of production, which cannot be separated by genders. Moreover, it cannot be concluded that one gender is more potential than the other to influence the audience in delivering speech. There are also other factors, particularly non-verbal factors, exist to give impacts on how a speech can influence the audience.The next researchers are suggested to conduct a similar research with different objects or to explore gender differences in language use by applying other approach. The next researchers might look into the gender differences in language use from literary works as well.